On Generalized Proportional Fractional Order Derivatives and Darboux Problem for Partial Differential Equations - Abdellatif Ben Makhlouf; Mondher Benjemaa; Djalal Boucenna; Lassaad Mchiri; Mohamed Rhaima (Discrete Dynamics in Nature and Society)
The study of the existence and uniqueness of solutions to 2D systems utilizing the generalized proportional fractional derivative operator is the focus of this work. We also derive a finite difference scheme in order to numerically approximate such an operator, and we prove that the method we propose is convergent. Several tests are performed at the end to illustrate the robustness of our algorithm.